Symptomatic Bipartite Patella: Three Subtypes, Three Representative Cases - Werner, Shawn; Durkan, Michael; Jones, Jackson; Quilici, Samantha; Crawford, Dennis (The Journal of Knee Surgery, 2013)
Bipartite patella can be classified into three unique subtypes; type I, II, and III. The following case series describes three representative cases of each subtype and a spectrum of location-specific treatment options for surgical care of the symptomatic bipartite patella.
Keywords: bipartite patella; synchondrosis; chondromalacia patella